Bronchial Mucoepidermoid Carcinoma: A Rare Cause of Chronic Respiratory Symptoms in Children - Case Report - João Nunes Caldeira; Mónica Jerónimo; Cláudia Piedade; Teresa Reis Silva (Publicaciones Permanyer, 2023)
Primary pulmonary tumors are uncommon in children. Mucoepidermoid carcinoma accounts for approximately 10% of all primary pulmonary neoplasms. This study reported the case of a 6-year-old male patient who presented with fever, cough, and wheezing, and had a history of choking and recurrent respiratory infections. Chest radiography showed a hyperinflated left lung, and bronchoscopy revealed a friable polypoid mass obstructing more than 90% of the left primary bronchus. Moreover, a chest computed tomography scan showed no lymphadenopathies. Endoscopic resection of the mass and posterior surgical resection of its remainder were performed. Histological examination revealed a low-grade mucoepidermoid carcinoma. Due to its rarity and the non-specific nature of symptoms, the diagnosis of mucoepidermoid carcinoma is usually delayed. In the presence of chronic respiratory symptoms and signs of bronchial obstruction on imaging exams, mucoepidermoid carcinoma should be included in the differential diagnosis, along with other more frequent conditions.